2018
DOI: 10.5694/mja17.00950
|View full text |Cite
|
Sign up to set email alerts
|

Psychological distress in remote mining and construction workers in Australia

Abstract: Objectives: To assess the prevalence and correlates of psychological distress in a sample of remote mining and construction workers in Australia. Design, setting: A cross‐sectional, anonymous Wellbeing and Lifestyle Survey at ten mining sites in South Australia and Western Australia, administered at meetings held during 2013–2015. Participants: 1124 employees at remote construction, and open cut and underground mining sites completed the survey. Main outcome measures: General psychological distress (Kessler Ps… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
93
1
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 94 publications
(101 citation statements)
references
References 7 publications
(21 reference statements)
6
93
1
1
Order By: Relevance
“…Firstly, not all these workers are men. More importantly, as reported by Bowers and her co‐authors in this issue of the MJA , 1 remote workers have a markedly higher level of psychological distress than the general Australian population.…”
mentioning
confidence: 60%
“…Firstly, not all these workers are men. More importantly, as reported by Bowers and her co‐authors in this issue of the MJA , 1 remote workers have a markedly higher level of psychological distress than the general Australian population.…”
mentioning
confidence: 60%
“…Psychological distress within the Australian mining industry is well documented 10,11,13,29 . Previous research has shown that metalliferous mining workers experience significantly greater levels of psychological distress when compared to a gender‐ and age‐weighted sample of employed Australians 11 .…”
Section: Discussionmentioning
confidence: 99%
“…Many studies examining psychological distress within rural and remote mining communities have often attributed FIFO commuting as one of the main contributing factors to the abnormally high levels of mental disorders experienced by these workers 29,35,36 . In 2013, the House of Representatives in Australia tabled its findings on the use of FIFO workforce practices in regional Australia 18 .…”
Section: Discussionmentioning
confidence: 99%
“…Senior employees are more likely to be perpetrators of bullying, which may moderate the relationship between bullying and psychosocial distress among FIFO workers [51]. In contrast to most other workplaces, FIFO workers are more likely to work night shifts and high compression rosters, which have been associated with psychosocial distress and therefore are important to investigate for confounding effects [64,65]. Another potential moderating factor is alcohol consumption, which has been associated with higher levels of psychosocial distress in FIFO workers [66].…”
Section: Introductionmentioning
confidence: 99%